Multiple Sclerosis Patients and Disease Modifying Therapies: Impact on Immune Responses against COVID-19 and SARS-CoV-2 Vaccination - Golshani, Maryam; Hrdý, Jiří (Vaccines, 2022)
This article reviews the literature on SARS-CoV-2 pandemic and multiple sclerosis (MS). The first part of the paper focuses on the current data on immunopathology of SARS-CoV-2 and leading vaccines produced against COVID-19 infection. In the second part of the article, we discuss the effect of Disease Modifying Therapies (DMTs) on COVID-19 infection severity or SARS-CoV-2 vaccination in MS patients plus safety profile of different vaccine platforms in MS patients.
Keywords: DMTs; multiple sclerosis; immunosuppression; SARS-CoV-2; COVID-19; vaccine